Its System to Manage Parking Supply: Considerations on Application to the “Ring” in the City of Brescia - Bulferetti, Susanna; Ferrari, Francesca; Riccardi, Stefano (TeMA - Journal of Land Use, Mobility and Environment, 2014)
Brescia’s downtown is outlined by link roads built up at the Venetian walls, known as “Ring. The “Ring” is characterized by high traffic flows, as well as by the presence of several paid parking lots located on and off street. Furthermore, several facilities are located on these link roads. Nowadays city of Brescia is equipped with an ITS system able to manage off street parking spaces, allowing the share of information about parking availability to potential users, through the use of variable message panels. The parking supply issue and its management are strongly felt by citizens, as well as many other cities communities, whether European or not. This contribution aims to encourage an integration of the existing ITS system for the off street parking management with additional devices, which allow to manage also the on street paid parking supply located on “Ring” roads. The minimization of so-called “shared traffic” component of traffic flows, as well as the increase of road safety, in the context of a medium-sized Italian city are the main objectives of the ITS system integration. ITS asset chosen for the Brescia case study springs from the analysis of some non-European experiences about on street parking management (for example, San Francisco and Boston) and certainly can be considered suitable for the parking supply management of the whole city. It could become the main starting point in Italian cities for the application of performance based parking pricing, widely experienced in many U.S. cities.